Caracteristicas audiológicas e psicoacústicas de pacientes com zumbido - Cruz, Ana Carolina Almendra (2018)
Introduction: Tinnitus is a symptom characterized by sound sensations originated without any external sound stimulus. It is usually associated with hearing loss. Objective: to describe the socio-demographic and psychoacoustic characteristics of adult patients with tinnitus. Method: Retrospective study of 581 medical records of patients with tinnitus. Data collected: sex, age, occupation, presence of hearing loss, location, duration and type of tinnitus, responses to acuphenometry, minimum level of masking (MML) and Analog-Visual Scale (VAS) 12. Results: Data showed that 62.31% were male and 37.69% female. 11.53% had a profession related to the heath sector, the rest were distributed almost equally among the other categories. The age distribution ranged from 17 to 88 years. 50,95% of the individuals have tinnitus in both ears, 6.37% in the head, 24.78% in the left ear and 17.90% in the right ear. Most have constant tinnitus (61.62%). Most patients did not have hearing loss. Among patients with hearing loss, more than 94% have bilateral, mild or moderate hearing loss. The duration of tinnitus has a distribution from 1 to 720 months. In the VAS the mean value was 6.05 and in the TBF-12 was 6.41. The mean values of Acufenometria were 6.3dBLS and MML 15.70 dBLS in the right ear and 14.28 dBLS in the left ear. Conclusion: Tinnitus affects men more often than women, regardless of the profession they have. The most referred site was both ears, constant and whistle type